The Existence of Wayang Orang Art Studio in Tembbelang Gunung Village, Lebakbarang District, Pekalongan Regency in Facing the Development of the Age - Lelyana Lely Aryani; Hartono Hartono; Malarsih Malarsih (Universitas Negeri Semarang, 2023)
The existence of the WAYANG Orang Art Studio is infuenced by people who tend to like things that are done continuously and for generations, so that eventually it becomes a habit that is still often carried out by the people of Tembbelang Village, Pekalongan Regency namely that the traditions or habits that are held in the village are still strong. Tembbelang in this modern era is to maintain the existence of the Wayang Orang art studio. The purpose of this study is to reveal the reasons for the Wayang Orang Art Studio to exist. This study uses a qualitative method that is a description of the object of research directly. Data collection techniques namely, observation, interviews, literature study, and documentation. The results of this study are to reveal the reasons for the continued existence of the Wayang Orang Art Studio today. The reasons in question are first, because of the holding of Wayang Orang art training amidst the influence of globalization. The training is believed to be a cornerstone for the continued existence of the studio, an awareness that the impact of existence is as a means of expression and channeling the hobbies of the supporterners of the arts themselves. Second, the have one common goals, which is to preserve the art of Wayang Orang in Tembbelang. Not only to preserve but to become a vessel for the survival of the Wayang Orang art. Nevertheless, this is a strong reason behind the existence of Wayang Orang art.